The Decompensating Pediatric Inpatient Simulation Scenarios: Case 4 - Septic Shock - Jimmy Beck; Amina Khan; Aisha Barber Davis (Association of American Medical Colleges, 2013)
Abstract Introduction This is a unique scenario in that it is focused on the initial recognition, management, and critical thinking involved in the decompensating inpatient rather than the code itself. In this case vital signs intentionally fluctuate dramatically to reflect reality to the degree that trainees can practice both their patient assessment skills and team communication skills. This done intentionally so as to not have a case scenario in which residents need to solely identify that the patient is in shock and then mechanically follow the pediatric advanced life support shock algorithm. Methods This is a case of an adolescent who was recently admitted for treatment of a left tibial osteomyelitis and develops rapidly evolving sepsis. This work is one of four simulation cases developed as part of a series of decompensating pediatric inpatient scenarios, designed for pediatric residents and medical students. During this simulation, learners practice proper IV access for fluid resuscitation and review initial signs of shock. They also have opportunities to review steps in assessment for shock, and determine when to escalate care based on patient assessment. Results Since implementation, learners have uniformly given positive evaluations indicating that they subjectively feel that their competence in the assessment and management of unstable inpatients is improving. Discussion The simulation environment provides the opportunity to assess learners' competency with specific skills when rubrics for evaluation are created and applied to similar scenarios. With practice, trainees will become increasingly proficient at timely recognition of sick patients and appropriate initial management, which will eventually improve educational, patient care, and safety outcomes.